Conseptualisation of category «behavior of the enterprise» in economic theory - Kapinus, Larisa; Skryhun, Natalya; Semenenko, Katerina; Kolodiuk, Svitlana (My University, 2021)
The study analyzes the prerequisites of the information society formation, which focuses on the new knowledge and ideas production, based on the advanced technologies and infocommunications use. It is established that the information society formation involves ensuring a high level of information and communication technologies development and the telecommunications market in general, which serve as the material basis of the transformational socio-economic processes. У дослідженні аналізуються передумови формування інформаційного суспільства, орієнтованого на нове знання та продукуванні ідей на основі передових технологій та використання інфокомунікацій. Встановлено, що формування інформаційного суспільства передбачає забезпечення високого рівня інформації та комунікації, розвитку технологій і телекомунікаційного ринку в цілому, які є матеріальною основою трансформаційних соціально-економічних процесів.
Keywords: кафедра маркетингу; enterprise; behavior of the enterprise; іnformation society; marketing environment; підприємство; поведінка підприємства; інформаційне суспільство; маркетингове середовище